ASSESSING GENETIC DIVERSITY OF PAKISTANI CITRUS VARIETIES USING MICROSATELLITE MARKERS - K. Shahzadi; S. Naz; S. Riaz (Journal of Animal and Plant Sciences, 2014)
Ten microsatellite markers i.e. Expressed Sequence Tag Simple Sequence Repeat (EST-SSR) markers were used to develop finger print profiles of sixteen Citrus cultivars. The DNA fingerprints were used to characterize the samples and detection of different level of polymorphisms. The total alleles identified were 64 with an average of 6.4 alleles / locus. Two markers i.e. TAA33 and BQ624307 gave minimum number of alleles (4) while one marker naming TAA41 detected the maximum alleles (11) and hence was the most polymorphic marker. The highest no. of alleles were observed in Tahiti lime where ten markers resulted in a total of 24 alleles. The lowest number of alleles was detected in two cultivars namely Meiwa and Eustis lime with 13 alleles each. To show the genetic relationship among varieties, the genetic dissimilarity values calculated by Ward’s minimum variance method were used to develop a dendrogram with DARwin software package v. 5.0.158.
Keywords: diversity; genetic markers; phylo-genetic relationship; microsatellites